The Effect of Brainstorming on audit Quality and its Reflection on Detecting the Risk of Fraud - حلو, جعفر عبد الحسين; محمد, صفاء احمد (Journal of Economics and Administrative Sciences, 2020)
Brainstorming is one of the fundamental and necessary concepts for practicing the auditing profession, as auditing standards encouraged the implementation of brainstorming sessions to reach reasonable assurance about the validity of the evidence and information obtained by the auditor to detect fraud, as the implementation of brainstorming sessions and the practice of professional suspicion during the audit process lead to increase the quality of auditing and thus raise the financial community's confidence in the auditing profession again after it was exposed to several crises that led to the financial community losing confidence in the auditing profession.The research aims to explain the effect of brainstorming as a contemporary concept in discovering the risks of fraud, as well as its role in improving the quality of auditing in Iraqi audit firms and offices, through a questionnaire form distributed to a sample of auditors in Iraqi audit firms and offices, and the number of distributed forms has reached (112) form. The effect of the variables was explained through the use of statistical models using the least-squares method and the linear regression model. After testing the research hypotheses a set of conclusions were reached, represented by the implementation of auditors in Iraqi companies and auditing offices for brainstorming sessions that contribute to improving the quality of audit by helping auditors accounts are to make better assessments of the risk of fraud, as auditors can start their assessments by looking at the signals of the fraud triangle hypothesis, and that using brainstorming sessions during audit planning increases the quality of the audit process by discovering the fundamental errors resulting from fraud or errors which lead to maintaining the confidence of the financial community in the auditing profession, the research recommended that the legislative and regulatory bodies in Iraq should emphasize the importance of peace, Describe the mental and the need for auditors to practice brainstorming during planning and implementation of the audit process, which leads to an increase in the quality of the audit.Type of research: research paper.